Community Potential in Early Childhood Development: Participatory Action Research - Chaichanasang, Tippharat; Jantanam, Wipaporn; Hungspruek, Umasamorn; Srisong, Pitaksin (Journal of The Royal Thai Army Nurses, 2021)
This Participatory Action Research (PAR) aimed to 1) study the situation of early childhood development in the community emphasis on the problems and the obstacles which involved in promotion of their early childhood development, 2) study the community potential model in promotion of early childhood development, and 3) study the effects of utilization of community potential model in promotion of early childhood development. The data were given by children and their family members, professional nurses, village health volunteers and nanny teachers from the child development center. Data collection was done by focus group interview, in-depth interview and participatory observation by using the process of participation in 3 phases of community potential development. The first phase is to study and assess the situation of early childhood development in the community to find out the problems and obstacles in promotion of their childhood development. The second phase is to develop the community potential model in promotion of early childhood development and the third phase is to evaluate the effectiveness of community potential model in promotion of early childhood development The result of situation analysis was found that 41.18 % of the children are in tendency of delay development and the language development both receptive language and expressive language development were most found 28.43%. The researchers participated with the group of the data givers in setting the model for developing the community potential model in promotion for early childhood development as follows: - 1) Training the parent in basic assessment DSPM. 2) Training nanny teachers in child development center for using toolkit in the DSPM and training the inventory skills for individual child development. 3) Increasing the potential of the health care officers in active services by home visit in every abnormality cases, assess the childhood development in all age level. and 4) Setting the data network system for developmental information for the children younger than 2-year-old before entering in the early childhood development center. After the community potential model in promotion of early childhood development was practiced, the result showed that the children who had tendency in delay development received the promotion in development and could have normal development in 30 days 19.05% and 80.95% could have normal development in 90 days. Conclusion was that the community potential model in promotion of early childhood development by using community participation can promote early childhood development to have their ordinary development as their proper age. The suggestion is that this model - the community potential model in promotion of early childhood development should be developed and used in other communities which had the same situation.